2008
DOI: 10.1523/jneurosci.5129-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Release in the Nucleus Accumbens Core Is Necessary for Heroin Seeking

Abstract: Long-term changes in glutamate transmission in the nucleus accumbens core (NAcore) contribute to the reinstatement of drug seeking after extinction of cocaine self-administration. Whether similar adaptations in glutamate transmission occur during heroin and cueinduced reinstatement of heroin seeking is unknown. After 2 weeks of heroin self-administration and 2 weeks of subsequent extinction training, heroin seeking was induced by a noncontingent injection of heroin or by presentation of light/tone cues previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
297
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(313 citation statements)
references
References 49 publications
14
297
0
2
Order By: Relevance
“…Although these findings are consistent with the localization of accumbal D 2 -likeRs on local glutamate terminals (see above), they are quite surprising considering that the extracellular glutamate levels in the nucleus accumbens are mainly sustained by nonvesicular glutamate release . In line with this view, several studies reported that the basal levels of extracellular glutamate in the nucleus accumbens are only modestly reduced or unaffected by tetrodotoxin perfusion or by the depletion of extracellular Ca + + levels Saulskaya and Mikhailova, 2002;Saulskaya and Soloviova, 2004;LaLumiere and Kalivas, 2008). Therefore, it seems unlikely that inhibition of synaptic release of glutamate is the main mechanism responsible for the reported extracellular glutamate reduction during quinpirole perfusion.…”
Section: Discussionmentioning
confidence: 85%
“…Although these findings are consistent with the localization of accumbal D 2 -likeRs on local glutamate terminals (see above), they are quite surprising considering that the extracellular glutamate levels in the nucleus accumbens are mainly sustained by nonvesicular glutamate release . In line with this view, several studies reported that the basal levels of extracellular glutamate in the nucleus accumbens are only modestly reduced or unaffected by tetrodotoxin perfusion or by the depletion of extracellular Ca + + levels Saulskaya and Mikhailova, 2002;Saulskaya and Soloviova, 2004;LaLumiere and Kalivas, 2008). Therefore, it seems unlikely that inhibition of synaptic release of glutamate is the main mechanism responsible for the reported extracellular glutamate reduction during quinpirole perfusion.…”
Section: Discussionmentioning
confidence: 85%
“…Oneway ANOVA revealed no significant effect of MPEP treatment on the active (F (3,20) =1.90, P=0.16) or inactive (F (3,20) =0.22, P=0.88) responses induced by cues ( Figure 4A). In addition, there was no significant effect of MPEP treatment on the active (F (3,20) =0.095, P=0.97) or inactive (F (3,20) =0.059, P=0.98) responses induced by heroin priming (0.25 mg per kg) with conditioned cues ( Figure 4B). …”
Section: Effects Of Mpep Microinfusions Into the Nac Shell On Heroin mentioning
confidence: 94%
“…It remains to be determined if these properties translate in the attenuation of symptoms for other anxiety disorders than social phobia (e.g., post-traumatic stress disorder, panic disorder) [66]. There are contradictory results as to CBD's effect on sleep (similar to results from animal studies) as it has been associated with both wake-inducing and hypnotic properties in humans [11,67,68]. Altogether, many pharmacological, preclinical, and clinical properties (e.g., antipsychotic, anxiolytic) of CBD that had been demonstrated over roughly the last decade all point towards a potential role for CBD in alleviating behaviors relevant to addiction disorder.…”
Section: Cbd and Neurobiological Targets/effectsmentioning
confidence: 99%
“…The glutamatergic system and particularly GluR1 receptors are known to contribute to neuroplasticity underlying drug-seeking behavior [67,73], and treatments targeting glutamates are being developed for addiction intervention.…”
Section: Cbd In Preclinical Addiction Modelsmentioning
confidence: 99%